Principles for evaluating knowledge co-production in natural resource management: Incorporating decision-maker values. (1st November 2019) - O'Connor, Ruth A.; Nel, Jeanne L.; Roux, Dirk J.; Lim-Camacho, Lilly; van Kerkhoff, Lorrae; Leach, Joan
Abstract: A key reason for undertaking transdisciplinary processes such as knowledge co-production in natural resource management is to access and apply different knowledge systems to complex issues. However, the value of co-production is predominantly framed by academics. They have focused on research design and outcomes in the form of 'science informing policy'. In this paper we build a more inclusive and holistic framing of knowledge co-production incorporating values of non-academic participants, and values related to the participatory process. Specifically, we examine how knowledge is communicated and deliberated upon and the requirements for this to be done effectively. We draw upon empirical data from interviews with natural resource managers who participated in two case studies of knowledge co-production in Australia and South Africa. Their perspectives are captured in eight evaluation principles that build upon existing evaluation frameworks for public participation. Critically, decision-makers valued science-based outputs not just as salient knowledge sources, but to give legitimacy to their decisions. This need for legitimacy necessitates transparency, fairness and inclusivity in knowledge selection, participation and dialogue within knowledge co-production processes. The practice-based knowledge of decision-makers was important for contextualizing and applying science to specific decision contexts. Another key finding is that communicative competence is central to the process of knowledge co-production because it enables participants to critically explore and understand the knowledge claims of others. Highlights: Decision-makers provide new perspectives on the value of knowledge co-production. Science is valued to both inform and legitimize decisions. Decision-makers' expertise is critical to apply science in specific decision contexts. Understanding and applying participant knowledge requires communicative competence. Transparent knowledge selection and inclusive dialogue promote legitimacy.